К изучению фауны саркофагин (Diptera, Sarcophagidae) Грузии - Гуджабндзе, М.Г. (Вестник зоологии, 1970)
The data are presented of faunistic investigation of Sarcophagidae in Georgia carried out in 1963—1965. In all 67 species of Sarcophagidae are registered which belong to 2 tribes, 6 subtribes, 19 genera and 21 subgenera. One of the species proved to be new for the USSR fauna and 26 —for Georgia. The article also provides supplementary data on the ecological grouping of Sarcophagidae and zoogeographic analysis oi the found species composition.